Mystical Writing, or the “Jouissance of Being” - Šumič Riha, Jelica (Filozofski vestnik, 2011)
Psychoanalysis’ primary aim is to reveal the emergence of the subject, beyond its identifications, as a response of the real. More specifically, psychoanalysis considers the realization of the subject as a response to the impossibility of the sexual relation. Claiming that “everyone is a poem”, Lacan signals that psychoanalysis aims not at that which is universal in the subject, but rather at what in the speaking being is most singular: the emergence of a way of enjoyment that would make up for the inexistence of the sexual relation. Taking up the articulation of writing and jouissance as a point of departure, the paper examines the mystical experience as a specific mode of such a making up. In so doing, the paper insists on the relation between jouissance and language in order to show to what extent the mystical experience can teach us about the possible ways of breaking with the lethal relationship with jouissance where one seems to be reduced to “the partner of one’s own loneliness”